The Double-Edged Sword Property of Mesenchymal Stem Cell-Derived Exosomal microRNAs in Colorectal Cancer - Yao, Hongliang; Sun, Caihua; Wang, Chengjun; Liu, Jipan; Li, Yun; Li, Li; Zhao, Bin; Liu, Jia (Turkish Journal of Gastroenterology, 2024)
Abstract Mesenchymal stem cells (MSCs)-based therapies are promising therapeutic strategies for cancer treatment, because of their strong immunomodulatory and tissue regeneration abilities. In case of colorectal cancer (CRC), MSCs indicate a double-edged sword activity. Some reports declared the inhibitory effects of MSCs on the proliferation, migration, and infiltration of cancer cells to suppress the CRC initiation and development, whereas others showed the tumor-promoter impacts of MSCs on the progression of CRC. Recent investigations have revealed that exosomal microRNAs (Exo-miRs) derived from MSCs (MSCs-Exo-miRs) are attributed to such paradoxical effect. Thus, the current review aimed to seek the role of MSCs-Exo-miRs in CRC progression and their therapeutic potential for the CRC treatment. Cite this article as: Yao H, Sun C, Wang C, et al. The double-edged sword property of mesenchymal stem cell-derived exosomal microRNAs in colorectal cancer. Turk J Gastroenterol. 2024;35(10):755-762.